Two Perspectives of the Galician Diaspora in Cuba: Miguel Barnet’s "Gallego" (1981) and Rosalía de Castro’s Social Poetry - Tasende, Mercedes (Madrygal. Revista de Estudios Gallegos, 2025)
The testimonial novel Gallego, by Cuban author Miguel Barnet, is intended to pay tribute to the thousands of emigrants who, beginning in the second half of the 19th century, left Galicia to seek their fortune in Cuba. However, the presence in the novel of five epigraphs taken from Cantares gallegos and Follas novas brings to light two contradictory perspectives on the Galician exodus to Cuba, destabilizing the reading pact, undermining the credibility of the protagonist’s testimony, distorting the supposed homage to the Galician group, and revealing the propagandistic nature of Barnet’s novel.